Energy Systems for Electric and Hybrid Vehicles - Chau, K. T. (IET transportation series, 2016)
Electric and hybrid vehicles have been globally identified to be the most environmentally friendly road transportation. This book provides comprehensive coverage of energy systems for electric and hybrid vehicles with a focus on the three main energy system technologies - energy sources, battery charging and vehicle-to-grid systems.